2023
DOI: 10.3390/ijerph20031869
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Process Risk Management of Soil Amendments for Remediation of Heavy Metals in Agricultural Soil—A Review

Abstract: Reducing the mobility and bioavailability of heavy metals in soils by adding exogenous materials is a technology for remediating soils contaminated with heavy metals. Unlike industrial sites, the use of such techniques in agricultural soils requires consideration of not only reducing the mobility of heavy metals but also avoiding adverse effects on soil fertility and the growth of plants. Due to the uncertainty of the stability of amendments applied to agricultural soil, the application of amendments in farmla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 99 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…At present, the common amendments are mainly inorganic, including lime; various shell powders; and industrial by-products (dolomite, fly ash, phosphate rock powder, alkali residue, etc.) [ 8 ]. Dimirkou et al [ 9 ] showed that goethite and clinoptilolite had a good adsorption effect on Cd and As.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the common amendments are mainly inorganic, including lime; various shell powders; and industrial by-products (dolomite, fly ash, phosphate rock powder, alkali residue, etc.) [ 8 ]. Dimirkou et al [ 9 ] showed that goethite and clinoptilolite had a good adsorption effect on Cd and As.…”
Section: Introductionmentioning
confidence: 99%